BRIDGING THE GAP BETWEEN MAQĀṢID AL-SHARĪ‘AH AND THE SDGs: CHALLENGES AND OPPORTUNITIES FOR SUSTAINABLE DEVELOPMENT - Hafidz Zainul Mustofa; Amin Wahyudi; Siti Marpuah (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2025)
The SDGs are designed as a universal and inclusive global development framework, but their implementation still lacks flexibility in accommodating the spiritual dimension and ethical principles. Based on quantitative indicators and material achievements, the SDGs approach ignores the moral, social, and spiritual aspects as the core of maqāṣid al-sharī‘ah. Therefore, this study seeks to analyze the alignment between the SDGs and maqāṣid al-sharī‘ah and proposes integrating Islamic values ​​to strengthen the moral, social, and ecological dimensions within the sustainable development framework. This research uses a systematic literature review analysis method, focusing on literature to explore integrating the maqāṣid al-sharī‘ah concept in sustainable development. The data sources in this study are journal articles, books, and other relevant documents. Sustainable development involves a multidimensional approach encompassing social, lifestyle, human resources, economic, environmental, and institutional dimensions. In the concept of maqāṣid al-sharī‘ah, this approach must balance the public interest, social welfare, and environmental protection by emphasizing the principles of justice and ethical and moral responsibility. Challenges in this implementation include integrating maqāṣid al-sharī‘ah values ​​with the SDGs, various interpretations of maqāṣid, economic and social challenges, climate change, and technological advancement. The integration of maqāṣid al-sharī‘ah with the SDGs shows alignment. It supports the achievement of welfare, but challenges, such as integration, interpretation, economic and social, environment, and technology, must be overcome for effective implementation. This study recommends strengthening sustainable development policies that consider maqāṣid al-sharī‘ah through education, technological innovation, and stakeholder collaboration.